2018
DOI: 10.1158/1535-7163.mct-17-1123
|View full text |Cite
|
Sign up to set email alerts
|

Antileukemic Efficacy of BET Inhibitor in a Preclinical Mouse Model of MLL-AF4+ Infant ALL

Abstract: -rearranged acute lymphoblastic leukemia (ALL) occurring in infants is a rare but very aggressive leukemia, typically associated with a dismal prognosis. Despite the development of specific therapeutic protocols, infant patients with -rearranged ALL still suffer from a low cure rate. At present, novel therapeutic approaches are urgently needed. Recently, the use of small molecule inhibitors targeting the epigenetic regulators of the MLL complex emerged as a promising strategy for the development of a targeted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Earlier studies demonstrated also synergies of BRD inhibitors with other drugs, such as CBP/p300 inhibitors acting synergistically with BET inhibitors as well as cytotoxic agents and dexamethasone in leukemia 34 . In addition, BET inhibitors showed synergy in cancer models in combination with HDAC inhibitors 8284 as well as kinase and PARP inhibitors 8587 . The combination of different inhibitors might also be important in overcoming drug resistance which has been observed in cells treated with BET inhibitors 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies demonstrated also synergies of BRD inhibitors with other drugs, such as CBP/p300 inhibitors acting synergistically with BET inhibitors as well as cytotoxic agents and dexamethasone in leukemia 34 . In addition, BET inhibitors showed synergy in cancer models in combination with HDAC inhibitors 8284 as well as kinase and PARP inhibitors 8587 . The combination of different inhibitors might also be important in overcoming drug resistance which has been observed in cells treated with BET inhibitors 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment of oxidative metabolism seems to also play a role in relapse in B-ALL (Dobson et al, 2020). We impaired MYC activity through inhibition of BET bromodomain proteins -an intervention that slows progression of MLL-driven leukemia -finding that this inhibitor blocked the conversion of CD34to CD34 + cells (Bardini et al, 2018;Dawson et al, 2011;Delmore et al, 2011). Together, our findings reinforce the notion that LICs are plastic and adaptable, providing possible explanations as to why therapies targeting LICs have yet to prove widespread efficacy despite being the object of intense investigation for over two decades (Pollyea and Jordan, 2017;Saygin et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…RUNX1 is known to be a putative target gene of MLL fusions, and was highly expressed in MLL-AF4 ALL cases, when compared with normal bone marrow cells (Guenther et al, 2008; Krivtsov et al, 2008). The BET inhibitor I-BET151, arrested the growth of MLL-AF4 infant leukemic cells in vitro through gene deregulation, including RUNX1 (Bardini et al, 2018).…”
Section: Discussionmentioning
confidence: 99%